Anesthesia, Outcomes, and Public Health: Changing Health Care While "Asleep". Issue 3 (1st May 2014) - Poeran, Jashvant; Mazumdar, Madhu; Memtsoudis, Stavros G.
Abstract : Abstract: More than 50 million surgical procedures are performed annually in the United States, with perioperative complications and related long-term adverse outcomes profoundly affecting the nation's health. A growing number of studies recognize that type of anesthesia, a main determinant of perioperative care, is associated with perioperative morbidity and mortality. Emerging data suggest, for example, that anesthesia may be a determinant of cancer recurrence after surgery. Further research is needed to elucidate the impact of anesthesia-related factors on short- and long-term health outcomes. Progress in this area of medicine and its public-health consequences will depend largely on the interest of the public, researchers, and health care policy makers.